2019
DOI: 10.14309/ctg.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Economic Burden in Hospitalized Patients With Cirrhosis: Analysis of a National Database

Abstract: INTRODUCTION: The prevalence of cirrhosis is increasing despite advances in therapeutics, and it remains an expensive medical condition. Studies examining the healthcare burden of inpatient cirrhosis-related care regardless of etiology, stage, or severity are lacking. This study aims to describe the current drivers of cost, length of stay (LOS), and mortality in hospitalized patients with cirrhosis. METHODS: Using the National Inpatient Sample (NIS) data from 2008 to 2014, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
95
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 25 publications
3
95
4
Order By: Relevance
“…Accurate coding of these is crucial to track patient outcomes, healthcare burden and economic impact of cirrhosis. 10 Similar to findings in VA data, 5 we found that ICD-10-AM codes for ascites, gastrooesophageal varices and HCC were relatively accurate. We also found the probability that patients without these codes didn't have these complications was very high for HCC (97.9%), but substantially lower for ascites (75.8%) and varices (75.5%).…”
Section: Discussionsupporting
confidence: 79%
“…Accurate coding of these is crucial to track patient outcomes, healthcare burden and economic impact of cirrhosis. 10 Similar to findings in VA data, 5 we found that ICD-10-AM codes for ascites, gastrooesophageal varices and HCC were relatively accurate. We also found the probability that patients without these codes didn't have these complications was very high for HCC (97.9%), but substantially lower for ascites (75.8%) and varices (75.5%).…”
Section: Discussionsupporting
confidence: 79%
“…HF is a growing public health problem due to increasing mortality rates and rising health care costs due to comorbidities like cirrhosis that require prolonged hospitalization and treatment with diuretics [ 7 , 8 ]. The common underlying pathophysiological mechanisms of ADHF and cirrhosis may explain why our patient cohort had a higher rate of mortality and a longer hospital LOS [ 9 11 ]. At the beginning of the disease cycle, patients with HF have a lowered cardiac output, whereas patients with cirrhosis undergo systemic arterial vasodilation that increases cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 This likely reflects that the patients in our study’s control group had portal hypertension, which is itself associated with higher HCRU and costs. 20 22 …”
Section: Discussionmentioning
confidence: 99%